(untitled) (Comprehensive Journal of Science, 2026)
This paper presents the design and implementation of a secure Dynamic Multipoint Virtual Private Network (DMVPN) architecture for enterprise networks with geographically distributed branches. Traditional site-to-site VPN solutions often suffer from scalability and management limitations as the number of branches increases [1], [2]. DMVPN addresses these challenges by enabling dynamic, scalable, and efficient connectivity between multiple sites over public networks [3]. The proposed architecture integrates Multipoint Generic Routing Encapsulation (mGRE), the Next Hop Resolution Protocol (NHRP), and the Open Shortest Path First (OSPF) routing protocol to provide dynamic routing and direct spoke-to-spoke communication [4], [5]. To ensure secure data transmission, IPsec encrypts tunnel traffic and protects network communications against potential threats [6], [7]. The solution is implemented and evaluated using the GNS3 network simulation environment [8]. Performance evaluation focuses on latency, throughput, and routing convergence time under normal operation and link failure conditions. Experimental results demonstrate that the proposed DMVPN architecture provides secure, flexible, and scalable connectivity while maintaining acceptable performance for enterprise requirements [7], [9]. Findings confirm that DMVPN, when combined with dynamic routing and robust security mechanisms, is an effective solution for modern enterprise wide-area networks [2], [5].